Využitie kinezioterapeutických metód pre zlepšenie pohybovej koordinácie a rovnováhy u pacienta po cievnej mozgovej príhode - Tóthová, Tamara; Havlová, Jana (Ošetrovateľský obzor, 2022)
Background: Among the most common problems in patients after a stroke, a disorder of balance and mo- vement coordination is associated with impaired self- -sufficiency. Goal: The aim of the work is to achieve improvement in the patient‘s overall balance and ability of self-ca- re using kinesiotherapeutic methods. Sample and methods: The criteria for patient selec- tion was that they had been two months after stroke, able to walk independently with or without the help of walking aids. Aspexy, palpation, sitting, standing and walking examinations were used to assess the pa- tient‘s health status. The neurological examination in- cluded tests of cerebellar function, reflexes, superficial and deep sensation, pyramidal extinction phenomena, and muscle tone according to the Ashworth scale. Standardized tests, such as the Functional Independence Test, the One-Leg Stand Test, the Time Up and Go Test, the Berg Functional Scale to assess postural sta- bility, and the Tinetti Scale to assess balance and gait were used. Results: A four-week application of kinesiotherapy methods led to a improvemed in balance and walking according to the Tinetti scale, to a improvement in postural stability assessed according to the Berg functional scale and functional self-sufficiency asses- sed according ti the FIM test. The results demonstra- ted the appropriateness of the selected kinesiotherapy methods. It is recommended to start rehabilitation as early as possible after the stroke, introduce regular exercise 2-3 times a week, do exercise patterns that strengthen the deep stabilization system, train without visual control and include training on an unstable platform
Keywords: výsledek terapie; Exercise Therapy; Postural Balance; Physical Therapy Modalities; Kinesiology, Applied; posturální rovnováha; Stroke; kineziologie aplikovaná; techniky fyzikální terapie; Rehabilitation; Treatment Outcome; cévní mozková příhoda; standardizované testy pro hodnocení rovnováhy; terapie cvičením; rehabilitace